(untitled) (Journal of the Management Sciences, 2025)
Aviation industry plays a significant role in both national and global economy. Hence, the need for aviation safety and security is sacrosanct. The study examined the role of the Nigeria Civil Aviation Authority (NCAA) in Safety and Security of Passenger. The study employed a descriptive design of qualitative method of research solely relying on a review of literature through the secondary source of data. The study revealed that the industry has significantly improved in recent time. However, the study found factors such as lack of autonomy, outdated security equipment and facilities, poor finance, insufficient security personnel training, and limited legislative authority pose a threat to the safety and security role of the NCAA. The study called for autonomy of NCAA, embracing and investing in new security measures and modern devices, and given due attention to the training and retraining of airport security personnel. Formalisation of judicial powers of enforcement of NCAA and the availability of funds were also recommended.